Integrative taxonomy of the Iberian Zodarion species of the rubidum and styliferum groups (Araneae: Zodariidae) - Shafaie, Sepideh; Pekár, Stano; Ortiz, David (Zootaxa, 2025)
Zodarion, one of the most diverse zodariid spider genera, has recently garnered significant interest due to its peculiar adaptations for stringent ant-eating specialization. However, species identification within this genus remains challenging, as many Zodarion species are still insufficiently documented. This study revisits the taxonomy of Iberian species within the rubidum and styliferum groups, which together comprise 25 of the 171 species in the genus. Detailed morphological documentation is provided, including photographs and SEM images of key taxonomic characters, presented here for the first time. Molecular characterizations were also conducted to facilitate future species identification and to investigate patterns of mitochondrial variation within and between species. Notably, Z. extraneum has been reinstated as a distinct species. The male of Z. extraneum and the female of Z. alentejanum are described for the first time, while the female of Z. viduum is redescribed. Additionally, the species Z. alentejanum, Z. bosmansi, Z. guadianense and Z. lusitanicum have been assigned to the styliferum group. Three new synonyms are proposed: Z. brevicephalus with Z. styliferum, Z. duriense with Z. bacelarae, and Z. parastyliferum with Z. extraneum. Pairwise interspecific divergences between individual sequences generally exceeded intraspecific variation, and the mitochondrial gene tree recovered all but one species as monophyletic groups, underscoring the utility of molecular barcoding for identifying Zodarion species. However, interspecific distances between consensus sequences often blurred species boundaries. Our integrative taxonomic study provides tools for improved identification of Zodarion species, facilitating further research into their biology.